EVOLUTION OF WORLD MONETARY SYSTEMS AND STAGES OF ITS DEVELOPMENT (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The world monetary system is an international monetary and credit system, formed as a result of the development of the world market and strengthened by agreements concluded between states. The main elements of the world monetary system are: national and world currency units in reserve, the mechanism of the gold ratio and exchange rates of currencies, the condition of mutual repayment, the volume of restrictions, the form of international settlements, the structure of the international currency and gold markets, the status of interstate monetary and credit organizations that manage currency relations, etc. There are 3 world monetary systems: